De la « transsubstantiation » discursive dans la traduction des textes médicaux - Walkiewicz, Barbara (Studia Romanica Posnaniensia, 2019)
Every specialist text carries traces of the institutionalized context in which it is created. The context is based on the socially sanctioned communicative relationship, on the strength of which discourse partners enter into a so-called communicative contract. A text is then a verbal realization of contractual obligations, strictly standardized at the level of genre. Hence, information about the status of the discourse partners and the nature of their contractual (communicative) obligations is essential for accurate interpretation of a text. This, in turn, places double responsibility on the translator, who is obliged not only to transfer the discourse object into the target language, but also to “present” the sender of the original to the recipient of the translate in such a way as to render their status and discourse characteristics. Failing that, the translator will not succeed in reconstructing the original discourse contract, and hence attaining functional coherence of the translation. The aim of this article is to examine whether, and to what extent, translators have managed to present communicating subjects of Polish hospital discharge summary to the French recipient.